HUMAN CAPITAL AND PERFORMANCE OF MICRO, SMALL AND MEDIUM ENTERPRISES: A LITERATURE REVIEW - Imelfina Musthafa; Elfindri Elfindri; Yulia Anas; Edi Ariyanto (Transpublika Publisher, 2024)
This research aims to examine aspects of human capital that influence the performance of Micro, Small, and Medium Enterprises (MSMEs). Drawing on an extensive review of literature from indexed journal databases, the study focused on identifying key factors related to